A theory-synthesized character pedagogical content knowledge (C-PCK) model for integrating character education into pre-service teachers' microteaching - Bangun Bangun; Eka Putri Saptari Wulan; Tumpal Richardo Sirait (Global Econedu, 2026)
This study develops a Character Pedagogical Content Knowledge (C-PCK) model by integrating Shulman’s Pedagogical Content Knowledge theory with Lickona’s Character Education framework to strengthen character integration in pre-service teachers’ microteaching. A qualitative library research design employing theory synthesis was conducted through systematic literature collection, critical review, comparative analysis, and conceptual integration of studies on PCK, microteaching, teacher competence, and character education. The proposed C-PCK model extends conventional PCK by incorporating moral awareness, ethical decision-making, value internalization, and professional role modeling into pedagogical competence, enabling character integration across instructional planning, implementation, reflection, and assessment. C-PCK provides a comprehensive theoretical framework for redesigning microteaching curricula, fostering pedagogical expertise alongside character-based professionalism to prepare prospective teachers as competent, ethical, and reflective educators.